KEGAGALAN INSTUTUSI, KORUPSI, DAN DAMPAKNYA TERHADAP EKONOMI INDONESIA ERA REFORMASI - Dwijaya Samudra Suryaman; Hastarini Dwi Atmanti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This study aims to analyze the effects of economic growth, government tax revenue, the Human Development Index (HDI), and poverty on the Corruption Perceptions Index (CPI) during the Reform Era in Indonesia over the period 1999–2022. Corruption is widely recognized as a factor that reduces the productivity of public expenditure, distorts resource allocation, and hampers economic growth. This study employs a multiple linear regression model using Indonesia’s time series data from 1999 to 2023. The dependent variable is the Corruption Perceptions Index (CPI), which reflects public perceptions of the level of corruption within a country; a higher CPI score indicates a lower level of perceived corruption. The independent variables in this study include economic growth, tax revenue, the Human Development Index (HDI), and poverty. The empirical results indicate that, simultaneously, the independent variables have a statistically significant effect on the dependent variable. Partially, economic growth and HDI exhibit a positive and statistically significant influence on the CPI, whereas tax revenue shows a negative and statistically significant effect. Meanwhile, the poverty variable does not have a statistically significant impact on the CPI. Furthermore, the goodness-of-fit test demonstrates that approximately 95% of the variation in the dependent variable is explained by the independent variables included in the model, while the remaining 5% is accounted for by variables outside the model. Keywords: Corruption Perceptions Index (CPI), economic growth, and poverty.